Knowledge hiding: impact of interpersonal behavior and expertise. Issue 2 (12th March 2018) - Lanke, Parijat
Abstract : Purpose: This paper intends to put forward the role of interpersonal (in)justice among co-workers and their individual expertise as important factors contributing to knowledge hiding behavior. The paper is written with an intent to explain a conceptual model for practitioners' benefit. The work is novel and covers the latest construct in the field of knowledge management and human resource management. Design/methodology/approach: A conceptual framework is elaborated with a brief explanation of the theory that helps explain it. The framework although being novel in itself, the explanation has been drawn from existing literature. Findings: If the co-workers do not treat each other with dignity and respect, it hampers their relationship. This in turn makes them hide knowledge from each other and at the same time if one of them holds an expertise power over the other, this behavior would be more enhanced. The whole relationship could be explained using social exchange theory. This holds implications for managers, especially when knowledge management is of paramount importance to a company for its sustenance. Practical implications: This work provides new insights into knowledge hiding behavior by employees. Certain ways to reduce this behavior are proposed. Originality/value: This paper is the one of the few written with an intent to bring knowledge hiding and its causes, to executives, in an easy to digest form. The concept is also newly introduced and these factors have not yet been brought up by any other researcher in the field.